2005
DOI: 10.1556/avet.53.2005.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics of some blood biochemical parameters in the growing turkey (Meleagris gallopavo)

Abstract: Blood serum clinical biochemical parameters of fasted BUT Big 8 male turkeys were determined at the ages of 3 days, 4, 8, 12, 16 and 20 weeks, for a follow-up of the developmental changes of some serum metabolites, enzymes and ions. The serum protein content (total protein, albumin, globulin) increased with age, indicating also the moulting-associated metabolic changes in the age interval from the 8th to the 12th weeks. Creatinine was shown to have a peak at 3 days of age (role of muscle activity in thermogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
8
27
0
2
Order By: Relevance
“…3) is a well-known process, being strongly associated with the somatic growth (mainly muscle tissue hypertrophic growth), as described in turkey poults by VASICEK et al (1991) andSZABÓ et al (2005). Basically, the total improving process ranged within the normal values published for broilers (MELUZZI et al, 1992;SHAHIN and ELAZEEM, 2005) and for Thai chicken (SIMARAKS et al, 2004).…”
Section: Serum Metabolites and Ionsmentioning
confidence: 63%
See 3 more Smart Citations
“…3) is a well-known process, being strongly associated with the somatic growth (mainly muscle tissue hypertrophic growth), as described in turkey poults by VASICEK et al (1991) andSZABÓ et al (2005). Basically, the total improving process ranged within the normal values published for broilers (MELUZZI et al, 1992;SHAHIN and ELAZEEM, 2005) and for Thai chicken (SIMARAKS et al, 2004).…”
Section: Serum Metabolites and Ionsmentioning
confidence: 63%
“…The reason for the measurement of the serum sodium concentration was basically not to detect differences between the to bird types, but to control the effects of possible dehydration. The well-known age-dependent concentration increase (in turkeys: VASICEK et al, 1991;SZABÓ et al, 2005) could be accurately detected, as well as its relationship with the increasing dry matter content of the body. Accordingly, a high positive correlation exists between the total body dry matter content and the serum sodium concentration.…”
Section: Serum Ion Concentrationsmentioning
confidence: 87%
See 2 more Smart Citations
“…3). Szabó et al (2005) demonstrated that high activities of alanine transaminase and aspartate transaminase and decreasing with age activity of alkaline phosphatase indicated the intensive growth and expressed muscle hypertrophy as a result of single-sided selection for meat production and high white glycolytic muscle mass. It may be speculated that the pre-slaughter handling, which includes catching, transport and hanging on shackles, is considerably a greater physical effort to heavy birds than to the turkeys of lighter lines.…”
Section: Discussionmentioning
confidence: 99%